Processo seletivo por competências dos gestores administrativos da Universidade Federal da Paraíba - Azevedo, Ana Julia Diniz (2023)
Society has been undergoing rapid transformations and public management needs to keep up with them. Considering the importance of the public service having competent managers who can help organizations achieve their goals, being the bridge between the other servants and the top management. The selection process for managers has also been reinventing itself and consists of a good management tool, as it seeks the candidate whose skills profile is most aligned with the organization's needs. Therefore, this research has as main objective to analyze the necessary elements for the accomplishment of the competence-based selection process for the administrative managers in the Federal University of Paraíba. And, to achieve the objectives of the work, qualitative research was carried out, through interviews with fourteen administrative managers of the UFPB. Then, data analysis was performed using the content analysis method. After analyzing the interviews, it was verified how the selection process occurs from the managers’ perception to occupy management functions, in addition to identifying the skills that they regard as essential for the occupants of the position. The development and training of managers emerged from the research data and proved to have the power to influence the result of the selection process for managers. Based on the results presented, guidelines were proposed for carrying out the selection of the next administrative managers. After the research, it was identified that, to carry out a selection process for administrative managers, the factors that may impact the appointment of the manager must be observed in advance. At the end of the study, it was observed that the selection process for administrative managers at the university is still in its initial phase and it is necessary to carry out several adjustments in the organization for its effective implementation. To ensure success in appointing the administrative manager, it is essential to follow the various stages of the selection process, considering the skills required for the position and, as a consequence, also to present better results for the organization. Finally, this work intends to help public organizations promote the selection process based on the competence of managers, in a more objective, isonomic and transparent way.